The Green Revolution: Social Change through Social Media - Tripathi, Veena; Bhattacharjee, Dhriti (International Journal of Social Sciences and Management, 2016)
The advent of the internet changed the way we communicate forever. It became such a potent force that it was recommended as a nominee for Time Magazine’s “Man of the Year.” The world became euphoric about how this technology was changing the way we think. The changes were being brought about by people and that they were the change agents. It is required to understand the key concepts behind the emergence of social change through social media and their support in creating sustainability. This paper will report a study of five Indian social campaigns, right from their birth to the phase where they were no longer within the control of their parent organization but became a movement in their own rights. It is an exploratory study aimed at understanding the way social media works and how private organizations can also bring about a public change. The study will cover social networking sites like Facebook, Twitter and organizational blogs. The variables will be drawn from the corporate sustainability reports, social media venues, working papers and other research studies. These factors and variables can be correlated to sustainability through which the objective to analyse the impact of social change through social media can be achieved. With sustainability becoming a mandate for big companies in India, this study will help in understanding how social media can play a decisive role in their sustainability policies. Int. J. Soc. Sc. Manage. Vol. 3, Issue-3: 146-152